Solubilization and Antitumor Activity of Oleanolic Acid Lysinate - Zhang, Lijuan; Zhong, Jialiang; Zhang, Yixin (Current Analytical Chemistry, 2016)
Objective: The aim of this study was to prepare and assess the solubilization and antitumor activity of oleanolic acid lysinate. Methods: Oleanolic acid lysinate was prepared as a potential antitumor pro-drug by co-grinding or rotary evaporating method. Characterization of oleanolic acid lysinate was achieved by X-ray powder diffraction, infrared spectroscopy, and differential scanning calorimetry techniques. Solubilization of oleanolic acid lysinate was measured by an HPLC method and the antitumor activity was assessed by the MTT method. Results: The results confirmed the formation of oleanolic acid lysinate. The water solubility was increased significantly. The antitumor activity of oleanolic acid lysinate was 9 times on HCT-8 and 8 times on A549 than that of oleanolic acid. Conclusion: The satisfactory water solubility and antitumor activity of oleanolic acid lysinate will be potentially useful for its application as a new pharmaceutical formulation in cancer treatment in the future.
Keywords: preparation